VISUALIZE VULNERABILITY MAP OF DENGUE INCIDENCES IN SELANGOR STATE USING GAUSSIAN MIXTURE MODEL - MATHUR, NIRBHAY (2016)
The denguedisease has been reportedas a majorcauseof mortality for the last 40 years worldwide including in Malaysia. According to the Malaysian Statistics Department, total reported number of dengue cases for the year 2008 to 2010 is 136,992 and it is increasing every year. According to Ministry of Health(MoH) of Malaysia, in urban area 77% of people are suffering from denguevirus compared to 23%people suffer in rural areas. Recent studies on dengue outbreaks measures on their serotype, epidemiology, weather forecasting and prediction modelling based on previous clustering. This projects investigates dengue incidences represent in spatial map with defined number of cluster. The study look into spatial- temporal mapping along with the clustering techniques which comes with k-mean as the initial step to generate the clusters of incidences and, K-NN techniques is applied to find best fit K- cluster values. Gaussian Mixture Model is applied to find density of the dengue incidences, where Kmeans is used to find the centroid of the incidences.